Bolehkah Guru Pendidikan Agama Islam Mengimbau Siswinya untuk Berjilbab? - Nadia Nur; Andi Arif Rifa'i (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
: This study reviews the third mandate in the Joint Decree of 3 Ministers (SKB 3 Menteri) concerning the Use of Uniforms and Attributes for Students, Educators, and Education Personnel in Schools Organized by Local Governments at the Elementary and Secondary Education Levels based on Law (UU) Number 20 of 2003 about the National Education System and Regulation of the Minister of Religion (PMA) Number 16 of 2010 concerning the Management of Religious Education in Schools. This research focuses on whether or not Islamic Religious Education teachers can encourage their female students to wear the hijab. This type of research is library research (library study) with documentation data collection techniques, by collecting various literature sources, such as copies of statutory documents, books, research journals, and articles from the internet related to this research topic. After the data is collected, it is analyzed using content analysis techniques. Based on a review of Law Number 20 of 2003 concerning the National Education System and Regulation of the Minister of Religion Number 16 of 2010, Islamic Religious Education teachers might encourage their Muslim female students to wear the hijab because it is a form of education.